2018
DOI: 10.3389/fneur.2018.00831
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Sensory Gating of the Primary Somatosensory Cortex Contributes to the Motor Circuit Dysfunction in Paroxysmal Kinesigenic Dyskinesia

Abstract: Paroxysmal kinesigenic dyskinesia (PKD) is conventionally regarded as a movement disorder (MD) and characterized by episodic hyperkinesia by sudden movements. However, patients of PKD often have sensory aura and respond excellently to antiepileptic agents. PRRT2 mutations, the most common genetic etiology of PKD, could cause epilepsy syndromes as well. Standing in the twilight zone between MDs and epilepsy, the pathogenesis of PKD is unclear. Gamma oscillations arise from the inhibitory interneurons which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
13
1
Order By: Relevance
“…However, the direction of those relationships was opposite to our expectations, with stronger neural gating of somatosensory sensations (more suppression) relating to higher subjective unpleasantness and intensity. This finding does not easily lend itself to explanation, as it stands in opposition to the theoretical account arrived at from the studies in schizophrenia and other pathologies, where reduced suppression is commonly found to relate to stronger symptom perception (Bak et al, 2017;Chan et al, 2012;Liu et al, 2018;Smucny et al, 2013). One possible explanation for this surprising finding is that our sample consisted of healthy young adults with no reported somatic or psychological complaints.…”
Section: Discussioncontrasting
confidence: 69%
“…However, the direction of those relationships was opposite to our expectations, with stronger neural gating of somatosensory sensations (more suppression) relating to higher subjective unpleasantness and intensity. This finding does not easily lend itself to explanation, as it stands in opposition to the theoretical account arrived at from the studies in schizophrenia and other pathologies, where reduced suppression is commonly found to relate to stronger symptom perception (Bak et al, 2017;Chan et al, 2012;Liu et al, 2018;Smucny et al, 2013). One possible explanation for this surprising finding is that our sample consisted of healthy young adults with no reported somatic or psychological complaints.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies have revealed a complex pattern of abnormalities affecting diverse subcortical regions including the basal ganglia and thalamus (Joo et al, 2005; Kim, Kim, Kim, Suh, & Koh, 2015; Shirane, Sasaki, Kogure, Matsuda, & Hashimoto, 2001; Zhou, Chen, Gong et al, 2010; Zhou, Chen, Zhang, et al, 2010), as well as cortical regions including the motor cortex, somatosensory cortex, presupplementary motor area and right inferior frontal gyrus (Hsu, Kwan, et al, 2013; Hsu, Liao, et al, 2013; H. F. Li et al, 2019; Liu et al, 2018) in PKD. However, the pathophysiological mechanisms in PKD are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, literature is lacking in exploring this aspect of the ERN in terms of relationships with the neural signatures of other events fitting this description, such as brief aversive bodily sensations. Instances of such EEG markers of bodily sensations include respiratory-related evoked potentials (RREP; Chan & Davenport, 2010), and somatosensory evoked potentials (SEP; Liu et al, 2018), both constituting stable and consistent evoked potentials that, like the ERN, are known to be affected by anxious states and trait negative affect (Chan, von Leupoldt, Bradley, Lang, & Davenport, 2012;Cheng et al, 2016;Chenivesse et al, 2014;Goffaux et al, 2011). Therefore, we examined potential links between the ERN and the neural correlates of brief, aversive respiratory and somatosensory events in healthy young adults.…”
Section: Introductionmentioning
confidence: 99%